Raven-II: An Open Platform for Surgical Robotics Research - Hannaford, Blake; White, Lee; Rosen, Jacob; Friedman, Diana W.; King, Hawkeye; Roan, Phillip; Cheng, Lei; Glozman, Daniel; Ma, Ji; Kosari, Sina Nia (IEEE transactions on biomedical engineering, 2013)
The Raven-II is a platform for collaborative research on advances in surgical robotics. Seven universities have begun research using this platform. The Raven-II system has two 3-DOF spherical positioning mechanisms capable of attaching interchangeable four DOF instruments. The Raven-II software is based on open standards such as Linux and ROS to maximally facilitate software development. The mechanism is robust enough for repeated experiments and animal surgery experiments, but is not engineered to sufficient safety standards for human use. Mechanisms in place for interaction among the user community and dissemination of results include an electronic forum, an online software SVN repository, and meetings and workshops at major robotics conferences.